Demonstrating the impact of your work - Hall, Robyn; Stieglitz, Tara (My University, 2014)
A growing number of websites provide ways to see how many times research and teaching materials have been cited, viewed, downloaded, and shared with others. Learn how to tell a story about the scholarly and social impact of your work using both traditional and alternative metrics when documenting accomplishments in CVs, dossiers, and funding applications. This hands-on session will include finding and interpreting metrics in Google Scholar, Scopus, ImpactStory.org, ResearchGate, and more.
Presented on September 16, 2014 at the Centre for the Advancement of Faculty Excellence (CAFE) at MacEwan University in Edmonton, Alberta.
Keywords: impact factor; altmetrics; bibliometrics; citation analysis